Finance and strategy - Villalonga, Belén (Emerald, 2014)
Strategy and finance are closely interrelated in the practice of management. With the increased informational demands resulting from regulatory changes such as Sarbanes Oxley and Regulation Fair Disclosure, the boundary between the roles of CEO and CFO has become blurred. Moreover, the global financial crisis has made the interdependence between corporate financial policies and firms strategies painfully salient. In academic research however, the two fields have by and large developed independently of each other. Advances in strategic management 31 (Finance and strategy) fills this gap with rigorous research papers that bridge the strategy and finance fields by building on them. It encompasses a range of combinations among the two main subdivisions of strategy researchcorporate strategy and business (competitive) strategyand the two main subdivisions of finance researchcorporate finance and capital markets. It includes theoretical and empirical contributions, and spans different underlying disciplines and research methodologies, consistent with the variety that exists amongst these two fields.
Keywords: Business planning.; Industrial management.; Strategic planning.; Finance.; elektronické knihy; electronic books